Perception of English Language Teachers Teaching in Mixed-Ability Classrooms in Community Schools: A Qualitative Case Study - Rayamajhi, Arjun Jung (BIC Journal of Management, 2025)
This study examines how English Language Teachers perceive teaching in mixed-ability classrooms within the context of community schools in Nawalpur District. During their teaching activities, what barriers do they face while teaching in mixed-ability classrooms? I employed the qualitative case study as a research design or methodology. The data were collected from interviews, personal stories of English Language Teachers, and experiences with open-ended questions asked to four English Teachers who have been teaching in mixed-ability classrooms at the secondary level, as well as classroom observations. The issues include diverse socio-cultural backgrounds, varying levels of proficiency, different learning styles, varied instructional techniques, and varying student numbers. Teachers have been facing many challenges and issues in addressing the needs of learners in mixed-ability classrooms. The collected data was analyzed under the Sociocultural Theory of Vygotsky (1978) and Constructivist Learning Theory (1950). Previous research and literature have not given in-depth attention to the challenges faced by English Language Teachers, focusing instead on differentiated instruction. This research reveals that teachers should adapt their pedagogical approaches to incorporate various instructional methods, as the learning pace and style differ among students. The class size, peer learning, and teachers’ scaffolding can also address the challenges they face in their classroom activities and improve and increase the student’s learning outcomes. Furthermore, it contributes to the current issue of mixed-ability classrooms by filling the gap in the existing literature and providing some solutions and guidelines to enhance students’ learning outcomes in community schools.